Studi Pola Aliran Distribusi Pemasaran pada Industri Konveksi Lokal di Desa Ledug, Kecamatan Kembaran, Kabupaten Banyumas - Rizki Nur Nadira; Anang Widhi Nirwansyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study carries an analysis related to the pattern of marketing distribution flow of the convection industry in Ledug Village through various levels of marketing channels. Three convection industries, namely Enjoy Apparel, Kayla Jaya Convection, and N Convection, are the main focus in this study. The data collected during the period of 2020 to 2023 becomes material for analysis to understand marketing strategies and adaptations made by the three actors in facing changes in market dynamics. The results of the analysis revealed significant differences in marketing strategy and performance among the three industry players. In zero and single-tier marketing channels, Enjoy Apparel was able to cement impressive distribution growth, reflecting responsive adaptation to fluctuations in domestic and international market demand. On the other hand, Kayla Jaya Convection and N Convection experience more complex performance variations, with repeated periods of increases and decreases. A deeper analysis of level two distribution channels reveals a more detailed shift in marketing strategy. While Enjoy Apparel continues to show steady distribution improvements, Kayla Jaya Convection faces a sharper decline, while N Convection remains at a steady level of performance. In this context, strategic adaptation and the ability to respond to market changes are emerging as decisive factors for maintaining competitiveness in a dynamic industrial environment.